PREVALENCE OF HEPATITIS B AND C INFECTIONS AMONG HOSPITALIZED RESPIRATORY PATIENTS: A TERTIARY CARE ANALYSIS FROM MULLANA, HARYANA - Dr. Mineshkumar Uttambhai Patel; Mr. Alok Pritam; Dr. Arunkumar Rameshwarprasad Varun; Dr. Shivanand M Gundalli (Journal of Population Therapeutics and Clinical Pharmacology, 2021)
Hepatitis B virus (HBV) and Hepatitis C virus (HCV) co-infections in respiratory patients represent a significant healthcare challenge in North India. The intersection of chronic liver disease and respiratory pathology creates complex clinical scenarios requiring specialized attention. Objectives: To determine the prevalence of HBV and HCV infections among hospitalized respiratory patients at a tertiary care center in Mullana, Haryana, and analyze associated risk factors and clinical outcomes. Methodology: A cross-sectional observational study was conducted from January 2019 to December 2020 among 384 hospitalized respiratory patients aged 18-75 years. Data collection included demographic profiles, clinical presentations, laboratory investigations including HBsAg and anti-HCV antibodies, and chest imaging findings. Statistical analysis was performed using SPSS version 26.0. Results: The prevalence of HBV infection was 12.8% (n=49) and HCV infection was 8.1% (n=31) among respiratory patients. Co-infection rate was 2.3% (n=9). Chronic obstructive pulmonary disease (COPD) patients showed higher hepatitis prevalence (18.4%) compared to pneumonia patients (9.2%). Mortality rate was significantly higher in hepatitis-positive respiratory patients (15.8% vs 6.2%, p<0.001). Conclusion: The study reveals substantial hepatitis burden among respiratory patients in Haryana, necessitating routine screening protocols and integrated management approaches in tertiary care settings.